Tiny Homes Are Huge for People Living With Serious Mental Illness. (October 2022) - Wilson, Amy Blank; Mahadevan, Thava; Villodas, Melissa; Rodriguez, Maria; Bailliard, Antoine; Cuddeback, Gary
Purpose: A formative evaluation examined the acceptability and feasibility of tiny homes for people living with serious mental illness (SMI).Methods: The evaluation included four focus groups with people with SMI and service providers ( n = 28) and eight overnight stays with people with SMI.Results: The analysis identified six recommendations for tailoring the design of the tiny homes and the community where the homes will be located to meet the needs of people living with SMI. The recommendations for the design of the tiny homes included maximize natural light and outdoor spaces, design flexible living spaces, and ensure accessibility. The recommendations for the design of the surrounding community included ensure privacy, build a community, and maximize residents' connectivity.Conclusions: This research serves as a starting point for interventions that aim to develop housing that is both affordable and tailored to the needs of people with SMI.